2017
DOI: 10.1038/srep41319
|View full text |Cite
|
Sign up to set email alerts
|

ERAMOSA controls lateral branching in snapdragon

Abstract: Plant forms display a wide variety of architectures, depending on the number of lateral branches, internode elongation and phyllotaxy. These are in turn determined by the number, the position and the fate of the Axillary Meristems (AMs). Mutants that affect AM determination during the vegetative phase have been isolated in several model plants. Among these genes, the GRAS transcription factor LATERAL SUPPRESSOR (Ls) plays a pivotal role in AM determination during the vegetative phase. Hereby we characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…For RT-qPCR analyses, 0.5-ÎŒg samples of total RNA were used for firststrand cDNA synthesis with the ImProm-II Reverse Transcription System, as already described by Mizzotti et al (2017). RT-qPCR profiling was carried out using the iQ SYBR Green Supermix (Bio-Rad) and the Bio-Rad iCycler iQ Optical System (software version 3.0a), with the primers listed in Supplemental Table S13.…”
Section: Nucleic Acid Isolation Cdna Library Preparation Rnaseq Anmentioning
confidence: 99%
“…For RT-qPCR analyses, 0.5-ÎŒg samples of total RNA were used for firststrand cDNA synthesis with the ImProm-II Reverse Transcription System, as already described by Mizzotti et al (2017). RT-qPCR profiling was carried out using the iQ SYBR Green Supermix (Bio-Rad) and the Bio-Rad iCycler iQ Optical System (software version 3.0a), with the primers listed in Supplemental Table S13.…”
Section: Nucleic Acid Isolation Cdna Library Preparation Rnaseq Anmentioning
confidence: 99%
“…For example, it was found that the formation of the AM in Antirrhinum majus requires ERAMOSA ( ERA ), a gene encoding a GRAS transcription factor (orthologous to LAS in Arabidopsis ). The basic role of ERA in AM formation is consistent with that of LAS/MOC1/ERA in preventing cell differentiation in the boundary area and in stimulating AM formation [ 57 ].…”
Section: Axillary Meristem Formationmentioning
confidence: 73%
“…S8 ). No member from the PINNA2 clade has been functionally characterized to date, but its sister LAS clade contains many functionally identified members, including rice ( Oryza sativa ) MOC1 ( Li et al 2003 ), tomato Ls ( Schumacher et al 1999 ), Arabidopsis LAS ( Greb et al 2003 ), snapdragon ( Antirrhinum majus ) ERAMOSA ( Mizzotti et al 2017 ), and strawberry ( Fragaria vesca ) LAM proteins ( Feng et al 2021 ) ( Fig. 4B ).…”
Section: Resultsmentioning
confidence: 99%